Evaluation of Magnetic Resonance Elastography and Transient Elastography for Liver Fibrosis and Steatosis Assessments in the Liver Transplant Setting - Melekoglu Ellik, Zeynep; Idilman, Ilkay S.; Kartal, Aysun; Balaban, Yasemin; Elhan, Atilla H.; Karcaaltincaba, Musturay; Ozkan, Hasan; Idilman, Ramazan (Turkish Journal of Gastroenterology, 2022)
Background: Liver graft fibrosis affects long-term graft and patient survival in liver transplant recipients. Transient elastography and magnetic resonance elastography are widely used for the assessment of liver fibrosis in routine clinical practice, but are limited in liver transplant settings. The aims of the present study were to evaluate the accuracy of magnetic resonance elastography and transient elastograph in the assessment of liver fibrosis in liver transplant recipients, and to determine the recurrence rates of post-transplant hepatic steatosis and liver fibrosis. Methods: A total of 126 consecutive liver transplant recipients were included. Magnetic resonance elastography and transient elastography were performed for to measure liver stiffness. Results: The most common cause of liver transplantation was hepatitis B virus-induced cirrhosis (50%). The mean liver stiffness value with transient elastography was 6.1 ± 3.0 kPa, and the mean magnetic resonance elastography value was 2.7 ± 1.0 kPa. A significant positive correlation was found between magnetic resonance elastography and transient elastography in terms of liver stiffness measurement (r = 0.61, P < .001). Obesity and the underlying etiology of liver diseases did not have any significant negative effect on magnetic resonance elastography and transient elastography measurements. During the follow-up, the post-transplant recurrence rates of hepatic steatosis and hepatic fibrosis were 26% and 37%, respectively. The recurrence rates of post-transplant hepatic steatosis and liver fibrosis were slightly higher in recipients with non-alcoholic fatty liver disease-related cirrhosis than those with viral hepatitisrelated etiologies (44% vs 27%, P = .43; 44% vs 30%, P = .45, respectively). Conclusion: Magnetic resonance elastography and transient elastography are accurate in assessing liver fibrosis in the liver transplant setting. Obesity and the underlying etiology of primary liver disease do not influence the measurements.